Bridging islands of knowledge: a framework of knowledge sharing mechanisms. (1st January 2003) - Chai, Kah-Hin; Gregory, Mike; Shi, Yongjiang
This paper attempts to answer the question of what and how knowledge sharing mechanisms should be used between geographically dispersed plants in multinational companies. Case studies in 11 multinational companies reveal that many mechanisms are used for inter-plant knowledge sharing, which are grouped into eight categories: transfer of people, forums (internal conferences/meetings), boundary spanners, periodicals, audits, benchmarking, best-practice guidelines and international teams. It is found that some knowledge sharing mechanisms are more suited for one stage of knowledge sharing than another, as determined by their "reach" and "richness". Specifically, mechanisms with high "reach" are more suitable for creating awareness among potential receivers and mechanisms with high "richness" are often more effective in transferring the knowledge. In addition, the choice of mechanism is also dependent on the degree of tacitness and embeddedness knowledge transferred. Based on these insights, a framework linking knowledge sharing mechanisms with knowledge transferred is constructed.